PENGARUH EKSTRAKURIKULER SENI TARI TERHADAP PEMBENTUKAN KARAKTER KREATIF SISWA SMA NEGERI 4 PEKANBARU - Da’iyah, Nadhrah ’Uqty Da’iyah Uqty; ', Hambali; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:This event will be based on research by the existence of extracurricular activities dance in SMA Negeri 4 Pekanbaru. Extracurricular dance art is an activity that is implemented outside of school lessons and is associated with beauty and rhythmic body movements followed by a resounding – sounds or music. Extracurricular dance is also a means for the development of creativity against the interest, talent and potential that exist in the student., therefore one establishment of creative character in the scope of the school's extracurricular program is art, especially the art of dance. Hence the formulation of the problem of the research is "How can the influence of extracurricular activities dance Towards the formation of Character  Creative students in SMA Negeri 4 Pekanbaru?", with the aim to find out how the influence of extracurricular activities dance towards the formation of character creative students in SMA Negeri 4 Pekanbaru. This research is useful for readers to add insight and information on character education.The method of this research is quantitative deksriptif. Data collection instruments used in this study i.e. the now consisting of 20 questions/ statement about influence of extracurricular dance (variable X) and 23 questions/ statement about the creative character of the students (variable Y). The data were analyzed using Linear Regression. With such a hypothesis stating "there are extra-curricular activities influence dance against the formation of creative character sman 4 Pekanbaru received.". This is evidenced by a series of simple regression test between variables X and Y variables, acquired Fhitung and Ftabel values are 12,47 >4, 10 obtained from the study of the distribution list Ftabel with the N39, at significant levels of 5, thus Ftabel, Fhitung or 12,47 >4, 10. So the hypothesis on this research accepted that there was a significant influence on extracurricular  activities    dance towards   the formation of character creative students in SMA Negeri 4 Pekanbaru. Key words: Influence, Extracurricular of  Dance, Creative Character of Students